Erosive tooth wear and use of psychoactive substances among Finnish prisoners - Raija Vainionpää; Kirsi Tuulaniemi; Paula Pesonen; Marja-Liisa Laitala; Vuokko Anttonen (BMC, 2019)
Abstract Background The aim of the study was to evaluate the prevalence and severity of erosive tooth wear (ETW) and its association with dental caries and the use of psychoactive substances among Finnish prisoners. Methods One hundred voluntary prisoners (90.9%) from the Pelso Prison participated in this cross-sectional clinical study between September 2014 and February 2015. Fifty prisoners were also interviewed using the one-on-one interviewing technique for their background factors and use of psychoactive substances. Basic Erosive Index (BEWE) (0-18) was used to measure erosive tooth wear. Decayed (D), missing (M), filled (F) and the number of remaining teeth (T) and DMFT were reported. The association between the different variables was tested and analysed by using cross tabulation. To test the association between the variables a logistic regression analysis was conducted. Results Almost all (90%) of the subjects had need for preventive and operative treatment for ETW. In addition, one in five (19%) suffered from severe erosive tooth wear. The use of psychoactive substances and pharmaceuticals is common, yet no association with ETW was found. Smoking and alcohol consumption were more common among younger prisoners than the older ones. There is an increased risk for ETW among older prisoners and major alcohol consumers. Past caries experience was associated with dental erosion. Conclusions Erosive tooth wear is common among Finnish prisoners in their thirties. ETW is associated with dental caries and daily alcohol consumption.